Effectiveness Of Online Learning and Physical Activities Study In Physical Education During Pandemic Covid 19 - Rohmad Apriyanto; Adi S (Universitas Bengkulu, 2021)
This study aims to determine the effectiveness of learning and physical activity in Physical Education with online media during the covid 19. Pandemic is a descriptive quantitative research about learning conditions using online learning. The population in this study SMA Plus Alfatimah students who carry out online learning. The samples in this study were Class X, XI and XII sample using total sampling. There are 346 respondes. The data collection instrument used online learning questionnaire used google form. Data analysis used descriptive statistics. The study showed that, students assessed physical education learning with online learning is very effective (8.3%) effective (36.9%) normal (40.2%) although there are also students who think ineffective online learning (11.6) very ineffective (2.9%). Result research on physical activity during the covid pandemic 19 (4.6) students do very high physical activity, (19.9%) in the high category. (69.7%) medium category and (5.8%) in low category. Types of sports activities that are conducted by students (65.1 °%) health sports, (23.2%) recreational sports, (9.1%) sports education, (2.6%) accomplishment sports. The habits of students has changes because this pandemic. Students are more often help parents activities at home. Habit changes due to during the pandemic, students do not live in school dormitories but in school respective homes. During online activities most of the students do not experienced significant impacts both physically and psychologically. Learners tend to be more interested in a mix of learning both online and offline. Students also have a deep level of interest use of certain online media used by educators. Learners also have an interest in the approach to using online learning methods.